An Examination of the Determinants of Ease of Doing Business: Perspectives from World Economies - ElDarawy, Omar (AUC Knowledge Fountain, 2024)
This thesis’ purpose is to explore the correlation between Ease of Doing Business sub-scores and the overall Ease of Doing Business score. The study includes a detailed quantitative study into the previously mentioned relationship. The Ease of Doing Business sub-scores comprise of scores representing starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting minority investors, paying taxes, trading across borders, enforcing contracts, and resolving insolvency. This is conducted via a series of diagnostic tests to identify an appropriate regression model. These tests include the Hausman Test, RESET Test, and Breusch-Pagan Test. Based on the tests, the method of regression selected used is the Generalized Linear Model (GLM). The results indicate that the following four of the ten sub-scores showed a positive, significant relationship with the overall Ease of Doing Business Score: Starting A Business, Getting Credit, Dealing With Construction Permits, and Resolving Insolvency. Starting A Business and Getting Credit obtained the strongest relationship with the overall score across quartiles. Additionally, this study provides insights into the modern venture capitalist and policymaker mindsets and approach to evaluation. This thesis aims to contribute to these approaches by adding depth to the existing literature and contributing to the ongoing, relevant dialogue.